P PENGARUH TERAPI ANTIKOAGULAN TERHADAP FAKTOR PEMBEKUAN DARAH PADA PASIEN DENGAN FIBRILASI ATRIAL - Nurhayati, Maulida Aisshella; Lukiyono, Yauwan Tobing (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2024)
Atrial fibrillation (AF) is the most common type of cardiac arrhythmia and can increase the risk of ischemic stroke due to the formation of blood clots. Anticoagulant therapy plays an important role in preventing thromboembolic complications in patients with AF. This study aims to systematically review the effects of anticoagulant therapy on blood coagulation factors in AF patients. The literature review was conducted by searching and analyzing scientific publications available in electronic databases such as PubMed, Scopus, and the Cochrane Library. The keywords used included “atrial fibrillation,” “anticoagulant,” “blood coagulation factors,” and other related terms. The selected studies comprised observational research and clinical trials that evaluated the effects of anticoagulant therapy on blood coagulation factors in AF patients. After screening, 25 studies were included for analysis. Most studies indicated that warfarin therapy significantly inhibited the extrinsic blood coagulation pathway, as indicated by an increase in the international normalized ratio (INR) and a decrease in prothrombin activity. In contrast, direct oral anticoagulants (DOACs) such as apixaban, rivaroxaban, and dabigatran did not show significant effects on the measured coagulation factors. Therefore, regular monitoring of coagulation parameters, particularly INR, in patients receiving warfarin therapy is essential to ensure therapeutic effectiveness and safety.